Antimycobacterial prophylaxis regarding Bacillus Calmette-Guérin -associated complications in children with primary immunodeficiency. (August 2022) - Ozsezen, Beste; Yalçın, Ebru; Ademhan Tural, Dilber; Sunman, Birce; Nayır Buyuksahin, Halime; Guzelkas, İsmail; Alboga, Didem; Aytekin, Elif Soyak; Esenboga, Saliha; Emiralioglu, Nagehan; Cagdas, Deniz; Doğru, Deniz; et al.
Abstract: Objective: Bacillus Calmette-Guérin (BCG) vaccine derived from Mycobacterium bovis can cause BCG vaccine associated complications (BCG-VAC) especially in patients with primary immunodeficiencies (PID). No consensus exists for antimycobacterial prophylactic therapy for patients with PID who receive the BCG vaccine. Aim: This study aimed to define the risk factors in the development of BCG-VAC and effect of antimycobacterial prophylaxis in PID patients vaccinated with BCG. Methods: This is a retrospective cohort study. 104 patients diagnosed with PID who received the BCG vaccination were referred to pediatric pulmonology in a single center were enrolled. The demographic characteristics, type, dosage and duration of antimycobacterial prophylaxis regimen, treatment modalities for BCG-VAC were documented. Regression analysis was performed to evaluate the effect of covariates for predicting BCG-VAC in patients with PIDs. Results: Among 104 patients 21 (21.2%) developed BCG-VAC. The frequency of BCG-VAC was highest in patients with Mendelian susceptibility to mycobacterial disease (46.2%) followed by patients with severe combined immunodeficiency (22.4%) and those with chronic granulomatous disease (9.5%). Prophylactic therapy against mycobacterium was initiated for 72 patients (69.2%). Among patients who received the antimycobacterial prophylaxis, BCG-VAC developed in only four patients (5.6%), whereas 17 patients (53.1%) developed BCG-VAC in the non-prophylaxis group and this difference was statistically significant (p < 0.001). Multivariable regression analysis with age at diagnosis, type of PID, receiving antimycobacterial prophylaxis, median T cell number at the time of PID diagnosis and HSCT status showed that not receiving antimycobacterial prophylaxis and lower median T cell number were predictors, with antimycobacterial prophylaxis having the highest odds ratio for BCG-VAC prediction in patients with PIDs (p:<0.001, R 2 :0.64). Conclusion: The lower frequency of BCG-VAC in our cohort can be explained by two main reasons; relatively late BCG vaccination schedule and receiving antimycobacterial prophylaxis. It is reasonable to begin antimycobacterial prophylaxis in patients with PIDs who are susceptible to BCG-VAC.